Impact of acute stroke unit on hospital length of stay. - Chen, L; McClaran, J; Buchan, A (2009)
Organized inpatient stroke care (stroke unit: SU) has become the gold standard in stroke care nowadays. The main purpose of this study was to evaluate the effects of implementing an acute stroke unit on the hospital length-of-stay (LoS) on the basis of discharge planning services. Oxford Radcliffe Hospital Trust (ORHT) founded an acute SU in 2005 and closed the rehabilitative stroke wards which have operated for years. Data of acute adult stroke patients admitted to ORHT from 2004 to September of 2005 were sorted to explore the impact of the acute SU on hospital LoS in addition to an active discharge planning program. In total, admission records of 1296 acute stroke patients were identified with the mean age of 73.9+/-13.3 years (range: 20-96 years) and the mean LoS of 25.6+/-37.1 days (median: 11 days). Regarding to the discharge destinations, 25.4% of them died, 48.8% patients returned home, 21.4% patients to community hospitals and 4.3% to various forms of institutional care. The SU admission rate among all acute stroke patients was 37.6%. The hospital LoS of acute stroke patients in ORHT was significantly shortened after the acute stroke unit was started in January 2005 (23.9+/-34.9 days in 2004 vs. 19.3+/-23.0 days in 2005, p=0.038) whilst the stroke mortality rate remained similar. Moreover, in-hospital rehabilitation rate (in geriatric wards of ORHT or community hospitals) was significantly reduced (30.4% vs. 40.9%, p<0.001). The acute SU showed an additional reduction of hospital LoS to the discharge planning program and significantly reduced the needs of in-hospital rehabilitation. Further investigation is needed to explore the impact of acute SU on patients' functional status.